1997
DOI: 10.1097/00001648-199709000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Birth Defects among Offspring of Norwegian Farmers, 1967-1991

Abstract: We investigated birth defects (N = 4,565) reported to the Medical Birth Registry of Norway among 192,417 births between 1967 and 1991 to parents identified as farmers in five agricultural and horticultural censuses between 1969 and 1989. The prevalences at birth of all and specific birth defects deviated little from those among 61,351 births to non-farmers in agricultural municipalities. We classified exposure indicators on the basis of information provided at the agricultural censuses. The main hypotheses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
120
2
10

Year Published

2000
2000
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(138 citation statements)
references
References 0 publications
6
120
2
10
Order By: Relevance
“…Two epidemiological studies reported a possible relationship between exposure to pesticides and hypospadias. Kristensen reported a moderate increase in the odds ratio (OR) for hypospadias in individuals exposed to farm chemicals (OR = 1.51, 95% confidence interval, 1.00-2.26) [66], and Weidner [67,68] A c c e p t e d M a n u s c r i p t sites has been associated with a high incidence of hypospadias [69,70]. Similarly, an increased rate of hypospadias was reported in boys from parents exposed to dioxin after the Seveso industrial accident [71].…”
Section: Ii-1 Arguments For An Environmental Contributionmentioning
confidence: 99%
“…Two epidemiological studies reported a possible relationship between exposure to pesticides and hypospadias. Kristensen reported a moderate increase in the odds ratio (OR) for hypospadias in individuals exposed to farm chemicals (OR = 1.51, 95% confidence interval, 1.00-2.26) [66], and Weidner [67,68] A c c e p t e d M a n u s c r i p t sites has been associated with a high incidence of hypospadias [69,70]. Similarly, an increased rate of hypospadias was reported in boys from parents exposed to dioxin after the Seveso industrial accident [71].…”
Section: Ii-1 Arguments For An Environmental Contributionmentioning
confidence: 99%
“…In a Danish study looking at cryptorchidism and hypospadias in the offspring of farmers and women gardeners, Weidner et al (94) found no risk for hypospadias but an increase for cryptorchidism. A Norwegian study looking at 192,417 births between 1967 and 1991, where the parents were identified as farmers, revealed an odds ratio of 1 for hypospadias (95). However, between 1967 and 1971, the odds increased to 2.06 among tractor sprayers.…”
Section: Human Epidemiologymentioning
confidence: 99%
“…Pastore et al (1997) showed a clear positive association between occupational exposure to pesticides, especially during early pregnancy, and the risk of stillbirths in California, and Kristensen et al (1997), associated central nervous system and limb defects with parental use of pesticide spraying equipment in Norway. In contrast, a case-control study in Holland determined little effect of pesticide exposure on the incidence of central nervous system defects in children of mothers involved in agricultural activities (Blatter et al 1996); environmental pollution with pesticides, regardless of the occupation of the mother, could have explained the increased risk of spina bifida found in this study.…”
mentioning
confidence: 99%